Approche hydrochimique de l’aquifère superficiel de ain djacer. Est algérien, Décembre - Djenba S; Boudoukha Abderahmane (Larhyss Journal, 2015)
Ain Djacer Area is the seat of an aquifer which is located in the alluvial deposits of Mio-Plio-Quaternary. This groundwater has to bedrock clays and gypsum marl Miocene, is surrounded by Cretaceous limestones which are limited to a fixed potential. It is a synclinal filled by sediments Mio-Plio-Quaternary where all flows converge toward the center of the plain. The intensive exploitation of groundwater resources in the region has greatly influenced the hydrodynamic and hydrochemical functioning of the shallow aquifer. This caused a decrease in the static level and mineralization of groundwater. To demonstrate the effect of this situation on the quality of groundwater, a hydrogeochemical study was conducted. This study showed that the calcium bicarbonate facies is near limestone and sodium chloride concentration in the center of the plain in liaison with the lithology. The thermodynamic analysis showed that the main geochemical processes involved in the acquisition of saline load are related to water-rock interaction (dissolution of carbonate and evaporate minerals), the cation exchange and concentrating along flow.